LEGAL EFFECTS ON NATIONAL ECONOMY - Yusep Mulyana (JEES: Journal of Economic Empowerment Strategy, 2020)
Legislation plays an important role in the economic development of a nation, but that the law can play a role in providing legal certainty for economic operators, the government as policy makers in the field of law. Determination of investment legislation in an effort to create a climate of investment, beginning with the presence of the Capital Market Law normatively accommodates the various interests of foreign investors. For example, there is the provision and maintenance of non-discrimination given to local entrepreneurs or the arena of domestic market share, investment protection and guarantees against nationalization and export risk threats, as well as the guarantee of the right to transfer profits or dividends. And the right to carry out legal settlement through international arbitration. Law in economic development, there are five elements that must be developed in the economic development of the nation, namely stability, prediction, justice, education, and in particular the development of law graduates (special development ability of the prosecutor) and the law should also have the ability to give an exact picture in situations or a future relationship conducted in the present. Both have procedural capability. Legislation that directly or indirectly impact on the economy and the legal system must provide a balance in awareness efforts to implement economic development. This is where the law becomes a very important factor in relation to the legal protection afforded by a country for investment activities. As revealed by Erman Rajagukguk that the main factor for the law can play a role in economic development is whether the law is able to create "stability", "predictability" and "fairness". The first two are the prerequisites for any economic system functioning. Included in the stability function (stability) is a potential law to balance and accommodate competing interests. The legal system and legal regulations to provide protection will create predictability, fairness and efficiency for investors to invest their capital. Act Investment in efforts to create an investment climate begins with Act Capital Markets normatively accommodate the interests of foreign investors and the legal concept as the basis for economic development, namely predictability, the ability procedural codification goals, education, the balance, the definition and clarity of status and accommodation